2016
DOI: 10.1155/2016/6981595
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Trimethyltin‐Induced Learning and Memory Deficits by 3,5‐Dicaffeoylquinic Acid

Abstract: The antiamnesic effect of 3,5-dicaffeoylquinic acid (3,5-diCQA) as the main phenolic compound in Artemisia argyi H. extract on cognitive dysfunction induced by trimethyltin (TMT) (7.1 μg/kg of body weight; intraperitoneal injection) was investigated in order to assess its ameliorating function in mice. In several behavioral tests, namely, the Y-maze, passive avoidance, and Morris water maze (MWM) test, 3,5-diCQA significantly ameliorated learning and memory deficits. After the behavioral tests, brain tissues f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 37 publications
4
44
0
2
Order By: Relevance
“…Therefore, in this study, we induced the oxidative stress injury in H9C2 by using TBHP, which is one of the most common oxidizing agents in experiments ( 28 ). In this study, we found that 3,5-diCQA showed a protective effect on H9C2 cells with an improvement of cell viability in a dose-dependent manner, which is in agreement with previous researches ( 26 , 27 ). These results demonstrated that 3,5-diCQA inhibits oxidative stress-induced apoptosis in H9C2.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, in this study, we induced the oxidative stress injury in H9C2 by using TBHP, which is one of the most common oxidizing agents in experiments ( 28 ). In this study, we found that 3,5-diCQA showed a protective effect on H9C2 cells with an improvement of cell viability in a dose-dependent manner, which is in agreement with previous researches ( 26 , 27 ). These results demonstrated that 3,5-diCQA inhibits oxidative stress-induced apoptosis in H9C2.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that 3,5-diCQA attenuated caspase-3 activation induced by H 2 O 2 , causing an increase in survival of SH-SY5Y cells in vitro ( 14 ). Consistently, 3,5-diCQA may prevent neuronal apoptosis through the repression of apoptotic signaling molecules such as Bax in vivo ( 26 ). In this study, we found that 3,5-diCQA was indeed able to reduce apoptosis induced by TBHP in H9C2 cells by improving the ratio of Bcl-2 to Bax and descending cleaved caspase-3, indicating that 3,5-diCQA inhibits apoptosis by suppression of the mitochondria-mediated intrinsic apoptosis pathway.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, 3.5-Dicaffeoylquinic acid was identified as a major component of Artemisia annua L. in an LC–negative ion ESI-MS total ion current (TIC) profile [ 33 ]. In our previous research, 3.5-Dicaffeoylquinic acid was analyzed by a Q-TOF MS system in ESI-negative mode and found to be a main phenolic compound of Artemisia argyi H. ethyl acetate fractions [ 34 ]. In other words, these results suggest that the physiological activity could be affected by components changed by Monascus purpureus fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Artemisia argyi is also one of the mugworts, and recently, its various physiological activities have been confirmed. In our previous research, it was confirmed that 3,5-dicaffeoylquinic acid (3,5-diCQA) and 4,5-diCQA were abundant in Artemisia argyi (Kang et al, 2016). 3,5-diCQA and 4,5-diCQA are isomers of diC-QAs, and they have superior antioxidant activity over chlorogenic acid, which is a well-known antioxidant.…”
mentioning
confidence: 78%